Efektivitas Dan Keamanan Terapi dengan Rejimen Bedaquiline dalam Terapi Multidrug-Resistant Tuberculosis (TB-MDR): Kajian Sistematis - Yana, I Gusti Agung Ari Kusuma (Brawijaya University, 2022)
MDR-TB is a tuberculosis disease caused by Mycobacterium tuberculosis which is resistant to isoniazid and rifampin with or without resistance to other first-line drugs. The development of drug-resistant tuberculosis is causing worldwide concern. Globally in 2019, almost half a million TB sufferers of which 78% had MDR-TB. In recent years, MDR-TB patients increased by 10% from 186,883 patients in 2018 to 206,030 in 2019. Bedaquiline has been recommended by WHO guidelines. Studies related to the effectiveness and safety of Bedaquiline are still few so that there is a need for qualified information to prepare a country, especially Indonesia, for the use of Bedaquiline therapy, especially since Indonesia is ranked second out of two-thirds of the total global TB. Objective: to describe the effectiveness and safety of Bedaquiline in combination therapy for the treatment of MDR-TB. Methods: The literature search was carried out independently by researchers using the online databases of Science Direct, Pubmed, and Cochrane without restrictions on the type of research and year of publication. The keywords used in this study were combined with Boolean operators, namely “bedaquiline” AND “tuberculosis” AND “multi-drug resistant”. Results: Seven studies met the inclusion criteria, the intervention of giving Bedaquiline for 24 weeks can reduce the average time of culture conversion by about 60-85 days. The percentage of culture conversion rate was higher with Bedaquiline (range 70-85%) than placebo (58%). The most common side effects are nausea and hyperuricemia. The majority of studies report a prolongation of the QT interval in patients treated with Bedaquiline. Conclusion: This systematic review showed that Bedaquiline is effective and safe to use in the treatment of MDR-TB. However, serious side effects of QT prolongation occurred in some respondents treated with Bedaquiline. Further studies need to be conducted to monitor the side effects of QT prolongation associated with the administration of Bedaquiline in the treatment of MDR-TB.